Shear Wave Elastography versus Strain Elastography in Diagnosing Parathyroid Adenomas. (17th March 2020) - Cotoi, Laura; Amzar, Daniela; Sporea, Ioan; Borlea, Andreea; Navolan, Dan; Varcus, Flore; Stoian, Dana
Abstract : Objectives . The aim of the study was to compare elastographic means in parathyroid adenomas, using shear wave elastography and strain elastography. Methods. This prospective study examined 20 consecutive patients diagnosed with primary hyperparathyroidism and parathyroid adenoma, confirmed by biochemical assay, technetium-99 sestamibi scintigraphy, and pathology report, after parathyroid surgery. All patients were examined on conventional 2B ultrasound, 2D shear wave elastography, and strain elastography. We determined using 2D shear wave elastography (SWE) the elasticity index (EI) in parathyroid adenoma, thyroid parenchyma, and surrounding muscle and examined using strain elastography the parathyroid adenoma, and determined the strain ratio with the thyroid tissue and muscle tissue. Results . All patients had positive sestamibi scintigraphy and underwent surgery, with confirmation of parathyroid adenoma in all cases. The mean parathormone (PTH) value before surgery was 153.29 pg/ml (36.5, 464.8) and serum calcium concentration was 10.5 mg/dl (9, 11.5). We compared using 2D-SWE and strain elastography parathyroid adenoma with thyroid tissue and with surrounding muscle. The mean EI measured by SWE in parathyroid adenoma was 4.74 ± 2.74 kPa and in thyroid parenchyma was 11.718 ± 4.206 kPa (mean difference = 6.978 kPa, p < 0.001 ), and the mean EI value in muscle tissue was 16.362 ± 3.829 kPa (mean difference = 11.622, p < 0.001 ). Using ROC analysis, we found that an EI below 7 kPa correctly identifies parathyroid tissue. We evaluated parathyroid adenomas using strain elastography by color mapping and strain ratio as a semiquantitative measurement; however, we could not find any statistical correlation comparing the strain ratio obtained from the parathyroid adenoma with the thyroid tissue (p = 0.485 ). Conclusion . Ultrasound elastography is a helpful tool in identifying parathyroid adenomas. A cutoff value below 7 kPa can be used in 2D-SWE. Color maps in strain elastography without adding strain ratio can be used, parathyroid adenoma being identified as score 1 in the Rago criteria.